Effects of drying treatments on functional properties of okara and extrusion processing of okara extrudates - Latip, Nur Adibah (2020)
Effect of extrusion process of okara and its product characterization in terms of microstructural and soluble dietary fiber were not found in previous studies, however these product characterizations are needed as knowing these characteristics are crucial as the information can be used in producing the best extruded product for further commercialization. The objectives of this research were to study the effects of drying conditions; hot air drying and vacuum drying at 40, 50, and 60°C, drum drying at 1 rotational speed with steam pressure of 2.0, 2.5 and 3.0 bar on physicochemical properties of okara. Water activity (0.41 - 0.50), L* (87.52 - 88.86), a* (1.04 - 1.66), and b* (13.11 - 16.84) of okara at all drying conditions tested showed a significantly higher (p < 0.05) values compared to Control (wet okara) with values of 0.95, 76.43, 2.39, and 20.85, respectively and it was considered safe from microbial growth and biochemical changes, while lighter colour may increase consumer acceptance. Okara processed using drum drying 2.0 bar (DD 2.0) showed a significantly higher (p < 0.05) swelling power (SP), water retention capacity (WRC) and oil retention capacity (ORC) compared to other drying conditions with values of 12.31 g/g, 10.69 g/g, and 3.73 g/g respectively, while vacuum dried sample at 60°C has the highest water solubility index (WSI) (16.67%). Based on physicochemical properties tested, DD 2.0 that produced dried okara with the highest SP, WRC, ORC, L*, a* with acceptable water activity (0.50), b* (14.38), total colour difference (ΔE) (12.90), and WSI (13.72%) were then chosen for extrusion study. The effects of different okara level (0, 5, 10, 15%) was studied in production of okara-enriched expanded snacks. Extrudate containing 15% okara had lower water activity (0.46) and higher insoluble, soluble and total dietary fiber (23.2, 1.2, 24.4%, respectively) compared to Control (0% okara) with values of 0.48, 0.5, 0.3, 0.8%, respectively. Extrudate with 5% okara that had a significantly higher L* (80.90) and expansion ratio (2.47), but lower a* (3.66), b* (18.22), ΔE (6.45) and bulk density of exrudates (0.23) compared to samples with 10 and 15% okara. In addition, the hardness and crispness of extrudate decreased with increasing okara level with higher percentage of okara exhibited a rougher surface with smaller size of air cells. The results indicated that incorporation of 5% okara able to produce expanded snack with improved nutritional quality while maintaining its extrudate characteristics.